2016
DOI: 10.1021/acs.jpcc.6b09386
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Absorption and Ultrafast Exciton Relaxation Dynamics in MAu24(SR)18 Clusters (M = Pt, Hg): Role of the Central Metal Atom

Abstract: Temperature-dependent and ultrafast transient absorption measurements were carried out to probe the optical properties and exciton relaxation dynamics in metal-doped (Pt and Hg) Au25 clusters. Optical absorption and electrochemistry results have shown that the Pt-doped cluster has a distinctly different HOMO–LUMO gap than that of Au25, while the gap did not change much for Hg-doped Au25. A decrease in temperature had resulted in much sharper absorption features as well as an increased number of absorption peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 49 publications
6
77
1
Order By: Relevance
“…For both platinum and palladium, the direct synthesis of Au24M(SR)18 0 (R = C2Ph, C6, C12) has been consistently described to yield clusters doped at the center. [12][13][14][15][16][17][18][19] For R = C4, we followed the same synthetic and purification protocol described for platinum by Qian et al 12 and adapted for palladium by Kwak et al. 14 MALDI-TOF mass spectrometry clearly indicated that the purified clusters only contain one foreign-metal atom, as shown in Figure S2 for Au24Pt(SC4)18 0 , and no contamination from residual Au25(SC4)18 − or Au25(SC4)18 0 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For both platinum and palladium, the direct synthesis of Au24M(SR)18 0 (R = C2Ph, C6, C12) has been consistently described to yield clusters doped at the center. [12][13][14][15][16][17][18][19] For R = C4, we followed the same synthetic and purification protocol described for platinum by Qian et al 12 and adapted for palladium by Kwak et al. 14 MALDI-TOF mass spectrometry clearly indicated that the purified clusters only contain one foreign-metal atom, as shown in Figure S2 for Au24Pt(SC4)18 0 , and no contamination from residual Au25(SC4)18 − or Au25(SC4)18 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Modification of the metal composition has been studied for several clusters, but most research has focused on Au25(SR)18, which is an atomically precise cluster that has been long considered a convenient benchmark system for understanding properties and devising applications of gold nanoclusters. 10,11 Controlled doping of Au25(SR)18 − has been carried out with the noble metals platinum [12][13][14][15][16] and palladium, 14,[16][17][18][19] and less noble metals, such as cadmium [20][21][22] and mercury, 15,[20][21][22][23] also because of the ease by which monodoping could be achieved with these metals as opposed to, say, copper and silver. 9 Mass spectrometry and single crystal X-ray crystallography were extensively employed to interpret the doping results and, particularly, assign the specific locations where these single foreign-metal atoms go.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 14 (Figure 16(a)) 148,286,507,568,603,706,721,767,768,791,795,813,826 and co-reduction method (Figure 16(b)). 43,58,174,219,222,241,262,300,305,311,346,356,431,536,587,601,614 In this study, we found that the isomer distribution also depends on the standing time in solution. As an example, Figure 17 shows the time dependence of the EI chromatogram of Au 25¹x Ag x (SC 4 H 9 ) 18 (x = 24) synthesized by the metalexchange method (Figure 16(a)).…”
Section: Dependence Of Isomer Distribution On Preparative Conditionsmentioning
confidence: 50%
“…Recent advances in the synthesis of thiolate‐protected gold nanoclusters have led to stable clusters with atomically precise core–shell structures . They exhibit unique optical, electrochemical, and catalytic properties that set them apart from other larger gold nanoparticle systems . Their PL properties, in particular, have been the focus of recent research interests .…”
Section: Introductionmentioning
confidence: 99%